IPv6 integration and coexistence strategies for next-generation networks. - Tatipamula, M. (IEEE Communications magazine)
IPv6 has been designed, among other things, to provide an expanded address space to satisfy the future networking requirements. In this article, we analyze and discuss important aspects of IPv6 deployment scenarios, and propose the system architecture coexisting and integrating with IPv4/MPLS networks. We investigate on various IPv6 deployment strategies along with network design examples, comparing these techniques. Then the IPv6 deployment in service provider environments is proposed.